Do active labour market policies for welfare recipients in Germany raise their regional outflow into work? A matching function approach - Rüdiger Wapler; Katja Wolf; Joachim Wolff (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2018)
While many studies estimated the effects of active labour market programmes (ALMPs) on the participants' labour market outcomes, much fewer studies are concerned with effects of these policies on the regional matching-process between job seekers and vacancies. An essential part of many reforms of the unemployment benefit system such as in Germany intended to activate unemployed job-seekers through an intense use of ALMPs. Therefore, it is crucial to understand whether such policies can improve the matching efficiency. We analyse quarterly panel data of German job centres in the period 2006 to 2011 and estimate the effects of the most important ALMPs on the regional exit rate from job-seeking into regular employment in a matching-function framework by applying the system generalized methods of moments estimator. Our results point to positive effects on the matching efficiency of a number of ALMPs, but the effects partly differ between high and low unemployment regions. Only for a few programmes does our evidence point to no or negative effects on the matching efficiency and this may be related to the implementation of these programmes on a very large scale. – – Viele empirische Studien haben die Effekte der Teilnahme an verschiedenen aktiven arbeitsmarktpolitischen Maßnahmen auf den Erfolg der Teilnehmenden am Arbeitsmarkt untersucht. Nur wenige empirische Studien haben sich mit Wirkungen dieser Maßnahmen auf den regionalen Matchingprozess zwischen Arbeitsuchenden und Vakanzen beschäftigt. Ein grundlegender Bestandteil vieler Reformen der Arbeitslosenunterstützung von Arbeitslosen, auch der Hartz-Reformen in Deutschland, war die Aktivierung von arbeitslosen Personen durch einen intensiven Einsatz aktiver arbeitsmarktpolitischer Maßnahmen. Folglich ist es von zentraler Bedeutung, die Wirkungen dieser Maßnahmen auf die Effizienz des Matchingprozesses zu verstehen. In dieser Studie werden Paneldaten der Jobcenter in Deutschland im Zeitraum 2006 bis 2011 auf Quartalsbasis verwendet, um mit einem Matchingfunktionsansatz die Effekte der quantitativ bedeutsamsten arbeitsmarktpolitischen Maßnahmen auf den Umfang der Abgänge aus Arbeitsuche in ungeförderte versicherungspflichtige Beschäftigung zu untersuchen. Die Schätzungen erfolgen mit der Generalisierten Momentenmethode. Die Befunde sprechen für einen positiven Einfluss einiger Maßnahmen auf die Matchingeffizienz. Nur für wenige Maßnahmen lassen sich keine oder negative Effekte auf die Effizienz des Matchingprozesses nachweisen, was damit zusammenhängen dürfte, dass die betreffenden Maßnahmen in sehr hohen Umfang eingesetzt wurden.
Keywords: C23; H43; J64; J68; 330; active labour market programmes; evaluation; regional unemployment; search theory; matching function